2008
DOI: 10.1515/bot.2008.036
|View full text |Cite
|
Sign up to set email alerts
|

A reassessment of Halophila species (Hydrocharitaceae) diversity with special reference to Japanese representatives

Abstract: In a recent review of the seagrass genus Halophila in Japan, eight taxa including four new species were listed: (i) H. decipiens, (ii) H. minor, (iii) H. major, (iv) H. ovalis, (v) H. mikii, (vi) H. nipponica, (vii) H. okinawensis, and (viii) H. gaudichaudii. In this study, the specific concept of Halophila in Japan as well as some other geographic areas was re-assessed by a combination of nuclear ribosomal ITS1, 5.8S rDNA, and ITS2 sequence analyses and morphological examinations of both recently collected ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 13 publications
5
46
1
2
Order By: Relevance
“…major is reported to be distributed in Western Pacific region including Vietnam, Indonesia, Malaysia and the Indian Ocean including Thailand and Myanmar either through the morphological or molecular information 12,19,20 . This study was the first report, which combined both morphological features and molecular information to identify H. major and suggested some key characters to identify this closely similar species.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…major is reported to be distributed in Western Pacific region including Vietnam, Indonesia, Malaysia and the Indian Ocean including Thailand and Myanmar either through the morphological or molecular information 12,19,20 . This study was the first report, which combined both morphological features and molecular information to identify H. major and suggested some key characters to identify this closely similar species.…”
Section: Discussionmentioning
confidence: 99%
“…These observations reveal that the taxonomic status of the group is still unclear. Besides, molecular studies by Uchimura et al 12 revealed that H. major occurred in Thailand, which was the first record of H. major in Thailand. A recent report by Nguyen et al 20 suggested the occurrence of H. major in Thailand; however its morphological features had never been examined.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations